Factors limiting plant recruitment in a Tropical Afromontane Forest - Abiem, Iveren; Dickie, Ian; Kenfack, David; Chapman, Hazel (Dryad, 2022)
Predicting how forest species composition may change in response to global
change is essential for meaningful management. Which species are most
likely to successfully recruit depends on a multitude of factors, but
processes operating at the seed-to-seedling transition being especially
important. Here we explore how insufficient seed dispersal (dispersal
limitation) and ecological filtering of seedlings (establishment
limitation) influence species recruitment in an Afromontane Forest. We
combined census data from seeds in seed traps and seed-seedling transition
plots in a Nigerian montane forest to measure dispersal and establishment
limitation across species, life history strategies and seed sizes. From
106 seed traps and 318 seedling plots we recorded 11,278 seeds from 38
species and 2,688 seedlings of 61 species. All species except for one
liana showed strong dispersal limitation while 23 out of the 30 species
showed establishment limitation. The two lianas sampled had significantly
lower dispersal limitation compared to the trees investigated in the
study. Our results suggest that both dispersal and establishment
limitation are markedly high in this Afromontane forest than would be
expected in a lowland counterpart.
Keywords: FOS: Biological sciences